New Models of Work Providement in the Conditions of the Digital Economy - Gasz, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
In the era of development of new technologies, flexible models of order fulfillment using digital platforms are becoming an increasingly popular form of providing work in various countries. Thanks to the possibilities created by the Internet, including the use of cloud technologies, people working independently can establish relationships with a selected contractor at any time and perform work remotely from anywhere in the world, while gaining access to the knowledge and organizational resources of the company. This phenomenon is becoming more widespread and is used in many areas of the economy. The research problem undertaken in the work is the changes in the modern labor market in the conditions of the digital economy. The aim of the study is to identify and characterize new models of work provision and conditions related to its performance. The work uses methods of analyzing the subject literature, descriptive analysis, statistical data analysis and comparative analysis.